The summer of the Danes - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael, 2021)
In the summer of 1144, a strange calm has settled over England. The armies of King Stephen and Empress Maud have temporarily exhausted each other. Brother Cadfael considers peace a blessing, but a little excitement never comes amiss to a former soldier and Cadfael is delighted to accompany his young friend, Brother Mark, on a mission of church diplomacy to his native Wales, not expecting to be caught up in yet another royal feud. The Welsh prince Owain Gwynedd has banished his brother Cadwaladr, accusing him of the treacherous murder of an ally. The reckless Cadwaldr has retaliated by landing an army of Danish mercenaries, poised to invade Wales and retake his lost lands. As the two armies teeter on the brink of bloody civil war, Cadfael is captured by the Danes together with a headstrong young woman fleeing an arranged marriage, but before he can untangle such domestic passions, Cadfael has to survive the brotherly quarrel that could plunge an entire kingdom into deadly chaos.